Efficient removal of dyes from aqueous solutions using short-length bimodal mesoporous carbon adsorbents - Moon, Soeun; Ryu, Jin; Hwang, Jongkook; Lee, Chang Gu (Chemosphere, 2023)
Ordered mesoporous carbons (OMCs) with controlled mesopore lengths and volumes were synthesized and investigated to remove the model dye methylene blue (MB) from aqueous solutions. The pore size, specific surface area, pore volume, and pore length of OMCs (CMK-3, sCMK-3, and sCMK-5) were analyzed and benchmarked against commercial activated carbon (AC). CMK-3 and sCMK-3 had narrow pore size distributions (PSDs) centered at ∼4.4 nm, whereas the PSD of sCMK-5 was bimodal, derived from the same pores as CMK-3 (∼4.4 nm) and the inner diameter of the carbon nanotubes (∼5.8 nm). The pore length decreased from 743 nm for CMK-3 to 173 nm for sCMK-3 and 169 nm for sCMK-5, facilitating the MB accessibility and efficient utilization of internal mesopores. The MB adsorption on the prepared adsorbents was well described by a pseudo-second-order kinetic model (R2 > 0.999), and the initial adsorption rate (h) on sCMK-5 was 34.07-fold faster than that on commercial AC. The Langmuir model adequately explained the equilibrium adsorption data, and the increase in the Langmuir maximal adsorption capacity (qm) of the OMCs was proportional to the specific surface area. The MB adsorption on sCMK-5 was endothermic and spontaneous, and proceeded primarily through physical adsorption as well as chemisorption reacting with oxygen atoms in hydroxyl groups. The prepared adsorbents were also suitable for polishing textile wastewater containing color-causing substances along with the background organic matter. These OMCs are promising for treating wastewater as efficient adsorbents for large molecular pollutants such as dyes.
Keywords: Adsorption kinetics; Bimodal mesoporous carbon; Carbon adsorbents; Commercial activated carbons; Mesopore; Methylene blue adsorption; Ordered mesoporous carbon; Pore length; Synthesised; Textile wastewater; Adsorption; Charcoal; Coloring Agents; Kinetics; Methylene Blue; Nanotubes, Carbon; Wastewater; Water; Water Pollutants, Chemical; Adsorbent; Adsorption kinetic; Ordered mesoporous carbon; Pore length; Textile wastewater